VD_FINDINFO Décision / 2014 / 595 vom 10. April 2014 - VD Tribunal cantonal (2014)
CONTRAVENTION, INDEMNITÉEN GÉNÉRAL, DOMMAGE, CLASSEMENT DE LA PROCÉDURE | 429 al. 1 let. a CPP (CH), 429 al. 1 let. b CPP (CH)